Colombia : Financial Sector Assessment Program-Technical Note-Crisis Management, Resolution, and Safety Nets. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The first mission of the Colombia FSAP was conducted virtually during June 1-21, 2021. This technical note focuses on the developments in the crisis management framework for the banking sector. The assessment examines the Colombian financial safety net and crisis management arrangements in light of the international best practices and standards on resolution and deposit insurance standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Colombia